Hereditary spastic paraplegia and prominent sensorial involvement: think MAG mutations!. Issue 8 (27th July 2019) - Roubertie, Agathe; Charif, Majida; Meyer, Pierre; Manes, Gael; Meunier, Isabelle; Taieb, Guillaume; Junta Morales, Raul; Guichet, Agnès; Delettre, Cecile; Sarzi, Emmanuelle; Leboucq, Nicolas; Rivier, François; et al.
Abstract: Homozygous mutations in MAG, encoding the myelin‐associated glycoprotein, a transmembrane component of the myelin sheath, have been associated with SPG 75 recessive spastic paraplegia. Here, we report the first patient with two compound heterozygous novel MAG mutations (p.A151V and p.S373R) and early developmental delay with a progressive complex phenotype characterized by spastic paraplegia, peripheral sensorimotor neuropathy, intellectual disability, and sensorial dysfunctions with severe optic atrophy and hearing involvement. Brain imaging showed progressive global cerebellar atrophy. We propose that complex hereditary spastic paraplegia, with axonal and demyelinating polyneuropathy, sensorial impairment and intellectual disability might suggest MAG mutations.